The App Save Yourself Improves Knowledge in Earth Environmental Emergency and Safe Behaviors - Sabina Maraffi; Francesco M. Sacerdoti (European Scientific Journal, ESJ, 2019)
Saving Yourself is an App from the methodological experience of Learning on Gaming, which is a new teaching approach: to learn while playing, that is different from Edutainment, designed both to educate and entertain, and Gaming to Learn, which consists of playing a game without specific didactic to outcome knowledge. With Learning on Gaming the game “hides” didactic inside the game: this could improve learning processes and, at the same time, renew teaching competences of mentors. Our experience is based on the application of Learning on Gaming to Digital Game Based Learning, through a Computer Class Role Playing Game (CCRPG). Adventure pathways of these CCRPG are focused on Earth Sciences and are interdisciplinary, multilingual and they are a good example of innovative teaching. As a CCRPG spin-off, “Saving Yourselves” is an App for Educators, Trainers, Teachers, Students, to know the earthquakes and volcanoes and strategies to reduce the risks associated with these phenomena. The App is intended to provide the most immediate and useful way to behave in the event of a geological emergency, with particular reference to volcanology emergency and seismic emergency. It can be used at school to optimize security education measures, but it can also be a game that is useful to rethink what has been learned. Saving Yourself is for all ages, because there are versions of the activity for kindergarten, primary school and secondary school and it is multilingual. It takes advantage of Games, ICT (Information and Communication Technologies), Innovative Teaching, to activate digital, scientific and technical skills.